(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective:To evaluate the initial effectiveness of the Health Education Program (HEP) in improving knowledge, self-care practices, and confidence in stoma care among patients at Da Nang Oncology Hospital, as well as identify factors contributing to these improvements. Materials and Methods: Aprospective study was conducted on 76 stoma patients undergoing inpatient treatment at Da Nang Oncology Hospital from January 2024 to December 2024. Participants engaged in the HEP, which included direct instruction, reference materials, and observational practice. Data were collected through interviews and skill assessments before and after the program. Results: Following the HEP, the proportion of patients with good knowledge of stoma care increased from 20% to 65, 8%. Correct self-care practices improved from 18.4% to 70,3%. Notably, patients’ confidence in self-care improved significantly, with the proportion of low-confidence patients decreasing from 75% before the program to 8% after the program. Side effects were predominantly mild and manageable. Conclusion: The HEP demonstrated significant effectiveness in enhancing knowledge, self-care skills, and confidence among stoma patients. It serves as a valuable solution to help patients better integrate into daily life and reduce the risk of complications associated with stoma care.